2022
DOI: 10.1021/acscatal.2c04085
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Organic Polymers with Anthraquinone Redox Centers for Efficient Photocatalytic Hydrogen Peroxide Production from Water and Oxygen under Visible Light Irradiation without Any Additives

Abstract: The photocatalytic generation of hydrogen peroxide (H 2 O 2 ) from H 2 O and O 2 under visible light irradiation is a hopeful approach to achieve solar-to-chemical energy transformation. While the lack of specific redox reaction centers is still the main reason for low photocatalytic H 2 O 2 production efficiency, herein, we present a conjugated organic polymer (AQTEE-COP) containing anthraquinone redox centers by Sonogashira cross-coupling reaction between 2,6-dibromoanthraquinone (AQ) and 1,1,2,2-tetrakis(4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 61 publications
(117 reference statements)
0
35
0
Order By: Relevance
“…This result further suggested that photocatalytic H 2 O 2 production occurs through sequential two-step single electron O 2 reduction, in which • O 2 – acts as an intermediate . The wavelength dependence of photocatalytic generation of H 2 O 2 showed that the trend of H 2 O 2 formation matched well with the absorption spectra of AQTB-COP and AQTT-COP (Figure c), indicating that the production of H 2 O 2 was triggered by light irradiation . For examining the heterogeneity of AQTB-COP and AQTT-COP, thermal filtration experiments proceeded (Figure S10).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…This result further suggested that photocatalytic H 2 O 2 production occurs through sequential two-step single electron O 2 reduction, in which • O 2 – acts as an intermediate . The wavelength dependence of photocatalytic generation of H 2 O 2 showed that the trend of H 2 O 2 formation matched well with the absorption spectra of AQTB-COP and AQTT-COP (Figure c), indicating that the production of H 2 O 2 was triggered by light irradiation . For examining the heterogeneity of AQTB-COP and AQTT-COP, thermal filtration experiments proceeded (Figure S10).…”
Section: Resultsmentioning
confidence: 86%
“…Both AQTB-COP and AQTT-COP exhibited signals at ∼182.1 and ∼91.6 ppm in the solid-state 13 C NMR spectra (Figure b), which are assigned to the carbonyl carbon atoms of anthraquinone moieties and carbon atoms of the internal alkyne moieties, respectively. While the wide peaks between 110 and 150 ppm are ascribed to the carbon atoms on phenyl rings . Moreover, the additional peak at ∼ 169.8 ppm in the solid-state 13 C NMR spectrum for AQTT-COP corresponds to the carbon atoms of the triazine ring.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen peroxide (H 2 O 2 ), one of the most valuable chemicals, is widely utilized in industries and the medical field . Production of H 2 O 2 via electrochemical 2e – -ORR is a cost-effective and eco-friendly route compared to the energy-intensive synthesis process with a mixture of oxygen and hydrogen and the waste-producing anthraquinone process. Some carbon-based electrocatalysts such as defective and heteroatom-doping carbon have been developed to drive the corresponding process. , Especially, carbon functionalized by oxygen , (such as ether and carboxylic acids) and nitrogen (such as graphitic, pyrrolic, and pyridinic nitrogen) exhibited excellent selectivity and productivity of H 2 O 2 . However, preparation under high-temperature pyrolysis not only leads to inevitable energy consumption but also brings impurity constituents, discounting their essential catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the open cavity of CMPs is well suited for the binding of small organic molecules, allowing them to access the exposed inner surface, where the transformations occur. Recently, the D–A molecular engineering strategy has been utilized for constructing CMP-based photocatalysts with highly efficient charge separation. For example, Bojdys et al found that the CMP photocatalyst incorporated stronger D–A interactions with shorter D–A pathways and featured efficient charge separation for water splitting . Despite the extensive research efforts on D–A type CMPs, works dealing with the engineering of D–A interactions and unveiling their influence on exciton binding energy for photocatalytic activity are still rare.…”
Section: Introductionmentioning
confidence: 99%